EFFECT OF FOLIAR SPRAY WITH " TECNOKEL AMINO Ca-B" SOLUTION AND SALICYLIC ACID ON YIELD PHYSICAL PROPERTIES OF PERSIMMON (Diospyros kaki L.) CV.FUYU - Meryer, Muhannad Rajab; Abdul Hayani, Ali Mohammed (Journal of agricultural, environmental and veterinary sciences, 2019)
The study was carried out during the growing season 2017 in one of the private orchards in Diyala Governorate/ Al-Khalis district/ Zanbour village, to study the effect of spraying with nutritious solution and Salsicylic acid on some physical properties of twenty years homogeneous size and growth fuiyu khaki trees planted at 3.5 x 3.5 m. A global experiment was applied using RCBD with four replicates (one tree for experimental unit). The experiment included the use of two-factor effect: the Tecnokel Amino Ca-B solution with four concentrations (0, 2, 4 and 6 ml L-1) and Salicylic acid (SA) in three concentrations (0, 200, 400 mg L -1), The results were statistically analyzed using the SAS program and the means were compared using Duncan’s multiple rangetest at a probability level of 0.05. The results can be summarized as follows: The spray treatments of the nutritious solution revealed that a concentration of 6 ml L by giving the highest values for yield physical properties like fruits number, weight, total fruit and fruit hardness, with an increase of 83.50%, 15.40%, 112.05% and 17.11% respectively for the treatment of water spray treatment, as well as increasing fruits set percentage at 55.66 compared with untreated control treatment. Spraying with salicylic acid resulted in significant differences. The highest concentration (400 mg L) gave the highest fruits number, weight, total fruit and fruit hardness with an increase of 9.33%, 5.15%, 15.81% and 3.47% respectively compared with untreated . The results of the spraying overlap of both factors revealed that the spray with highest concentration of each of them gave the highest values of the fruits set percentage, fruits number, weight, total fruit and fruit hardness) 66.51 fruit tree-1, 92.07 g fruit-1, 41.66 kg tree-1 and 3.55 kg cm-2) compared with untreated control treatment.